The Eurozone Crisis : How Banks and Sovereigns Came to Be Joined At the Hip - Sandri, Damiano (IMF Working Papers; Working Paper ;, 2011)
We use the rise and dispersion of sovereign spreads to tell the story of the emergence and escalation of financial tensions within the eurozone. This process evolved through three stages. Following the onset of the Subprime crisis in July 2007, spreads rose but mainly due to common global factors. The rescue of Bear Stearns in March 2008 marked the start of a distinctively European banking crisis. During this key phase, sovereign spreads tended to rise with the growing demand for support by weakening domestic financial sectors, especially in countries with lower growth prospects and higher debt burdens. As the constraint of continued fiscal commitments became clearer, and coinciding with the nationalization of Anglo Irish in January 2009, the separation between the sovereign and the financial sector disappeared.